Electrically-detachable epoxy resin adhesive as well as preparation method and application thereof

By introducing specific solid electrolytes and coupling agents into epoxy resin adhesives, the shortcomings of existing epoxy resin adhesives in terms of bonding strength, heat resistance and high temperature and high humidity resistance are solved, and high bonding strength and goodness are achieved. Heat resistance, suitable for high-reliability bonding and glue removal needs of electronic products.

CN119463772APending Publication Date: 2025-02-18XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767989.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing electrically disassembled epoxy resin adhesives have shortcomings in their bonding strength, heat resistance and high temperature and high humidity resistance, which limits their promotion and use in electronic products.

Method used

By introducing specific oxide-based solid electrolytes and/or sulfide-based solid electrolytes and coupling agents into epoxy resin adhesives, the ratio of epoxy resin, solid electrolytes and coupling agents is regulated, and the bonding strength of the adhesive is improved and Heat resistance.

Benefits of technology

It realizes high bonding strength, good heat resistance and high temperature and humidity resistance of epoxy resin adhesives, and has electrical disassembly performance, which is suitable for electronic products that require high bonding reliability and glue removal function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169485430000121
    Figure BDA0005169485430000121
Patent Text Reader

Abstract

The invention belongs to the field of epoxy resin adhesives, and particularly relates to an electrically detachable epoxy resin adhesive as well as a preparation method and application thereof. The epoxy resin adhesive contains epoxy resin, a solid electrolyte, a coupling agent, and an optional curing agent, toner, inorganic filler and auxiliaries. The solid electrolyte is an oxide solid electrolyte and / or a sulfide solid electrolyte; the mass ratio of the epoxy resin to the solid electrolyte to the coupling agent is 100: (10-150): (1-15). The epoxy resin adhesive provided by the invention has electrical disassembly performance, has the advantages of high bonding strength and good heat resistance and high-temperature and high-humidity resistance, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of epoxy resin adhesives, and in particular relates to an electrically disassembled epoxy resin adhesive and a preparation method and application thereof. Background Art

[0002] Epoxy resin adhesives are well-known in electronic products for their excellent bonding properties, and therefore are used in various important electronic devices. However, with the global requirements for environmental protection and energy conservation, many important electronic components need to disassemble some of the bonded parts for reassembly, repair and recycling during the actual production process. However, due to the strong bonding properties of epoxy resin adhesives, these used electronic components are attached with residual adhesive on the surface, which makes them unable to be recycled, thus causing serious waste. In recent years, there is a technology that adds alkali metal salts and solvated matrix to epoxy resin adhesives to form liquid electrolytes, thereby giving epoxy resin adhesives the function of being disassembled under power-on conditions, thereby achieving gentle disassembly without damaging the electronic bonding substrate. However, although the existing power-on disassembleable epoxy resin adhesives have the function of being disassembled under power-on conditions, they still have a large gap with the traditional widely used epoxy resin adhesives in terms of bonding strength, heat resistance, high temperature and high humidity resistance, etc., which limits the promotion and use of such electrical disassembly epoxy resin adhesives. Summary of the invention

[0003] The first purpose of the present invention is to provide an electrically disassembled epoxy resin adhesive with high bonding strength and good heat resistance and high temperature and humidity resistance, in view of the shortcomings of the prior art electrically disassembled epoxy resin adhesive, which has poor bonding strength and poor heat resistance and high temperature and humidity resistance.

[0004] The second object of the present invention is to provide a method for preparing the above-mentioned epoxy resin adhesive.

[0005] The third object of the present invention is to provide application of the above epoxy resin adhesive in bonding electronic products.

[0006] Specifically, the epoxy resin adhesive provided by the present invention contains epoxy resin, solid electrolyte and coupling agent and optional curing agent, color powder, inorganic filler and auxiliary agent; the solid electrolyte is an oxide solid electrolyte and / or a sulfide solid electrolyte; the mass ratio of the epoxy resin, solid electrolyte and coupling agent is 100:(10-150):(1-15).

[0007] The preparation method of the epoxy resin adhesive provided by the invention comprises the steps of uniformly mixing epoxy resin, solid electrolyte and coupling agent as well as optional curing agent, color powder, inorganic filler and auxiliary agent to obtain the epoxy resin adhesive.

[0008] In existing epoxy resin adhesives, the detachable performance is usually achieved by adding liquid electrolytes. However, although the use of liquid electrolytes can give epoxy resin adhesives the performance of being electrically detachable, it will seriously affect the bonding strength of epoxy resin adhesives. In this regard, after in-depth research, the inventors of the present invention found that one of the main reasons for the substantial decrease in the bonding strength of epoxy resin adhesives is that: liquid electrolytes are liquid substances and are difficult to solidify. After the epoxy resin adhesive is completely solidified, the uncured liquid electrolyte will remain in the curing system to form a "plasticizer", which changes the internal structure of the curing system. The presence of this "plasticizer" has a large negative impact on the bonding strength and will significantly reduce the bonding performance of the epoxy resin adhesive; in addition, due to the poor compatibility between inorganic solid electrolyte materials and organic epoxy resin adhesives, it is usually difficult to evenly disperse in the epoxy resin adhesive system, which limits its application in electrically disassembled epoxy resin adhesives.

[0009] The key to the present invention is to disregard the limitation of the traditional concept that inorganic solid electrolytes are difficult to be evenly dispersed in the epoxy resin adhesive system and should be used with caution. A specific solid electrolyte (oxide solid electrolyte and / or sulfide solid electrolyte) is introduced into the epoxy resin adhesive system in the presence of a coupling agent, and the ratio between the epoxy resin, the solid electrolyte and the coupling agent is regulated. The epoxy resin adhesive thus obtained not only has the property of being electrically disassembled, but also has the advantages of high bonding strength and good heat resistance and high temperature and high humidity resistance. It is speculated that the reason may be that: the oxide solid electrolyte and / or sulfide solid electrolyte itself has a high ionic conductivity in the solid state, and can undergo Faraday electrochemical reaction under power-on conditions, weakening the bonding force at the adhesive bonding interface, thereby giving the epoxy resin adhesive detachable properties, and the two specific solid electrolytes, the oxide solid electrolyte and / or sulfide solid electrolyte, have good compatibility with the epoxy resin adhesive under the synergistic effect of the coupling agent, and can be well dispersed in the epoxy resin adhesive system. At the same time, the oxide solid electrolyte and / or sulfide solid electrolyte will not cause the epoxy resin adhesive to form a "plasticizer" after curing, causing its internal structure to change and affect the bonding strength. On the contrary, the oxide solid electrolyte and / or sulfide solid electrolyte itself can also serve as a filler to reinforce the colloid, thereby improving the bonding performance of the epoxy resin adhesive and improving the bonding strength, heat resistance, and high temperature and high humidity resistance. In summary, the epoxy resin adhesive provided by the present invention is not only electrically disassembled, but also has high bonding strength and good heat resistance, high temperature and high humidity resistance, providing a solution idea, product and method for application scenarios with high requirements for bonding reliability and the need for adhesive removal in actual production processes. DETAILED DESCRIPTION

[0010] The epoxy resin adhesive provided by the present invention contains epoxy resin, solid electrolyte and coupling agent and optional curing agent, color powder, inorganic filler and auxiliary agent. The present invention aims to introduce specific solid electrolyte and coupling agent into the epoxy resin adhesive system so that the adhesive can be peeled off from the bonding interface under voltage application, thereby achieving the effect of electrical disassembly. The epoxy resin adhesive can be peeled off from the bonding interface when power is applied, thereby improving the recovery rate of electronic components. Wherein, the mass ratio of the epoxy resin to the solid electrolyte is preferably 100:(10-150), such as 100:10, 100:20, 100:30, 100:40, 100:50, 100:60, 100:70, 100:80, 100:90, 100:100, 100:110, 100:120, 100:130, 100:140, 100:150 or any value therebetween. The mass ratio of the epoxy resin to the coupling agent is 100:(1-15), such as 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15 or any value therebetween.

[0011] In the present invention, the content of the epoxy resin is preferably 15 to 35 parts by mass, such as 15, 17, 20, 22, 25, 28, 30, 32, 35 parts by mass or any value therebetween; the content of the solid electrolyte is preferably 5 to 20 parts by mass, such as 5, 8, 10, 12, 15, 18, 20 parts by mass or any value therebetween; the content of the coupling agent is preferably 0.5 to 2 parts by mass, such as 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2 parts by mass or any value therebetween; the content of the curing agent is preferably 5 to 20 parts by mass. The content of the toner is preferably 0.1-1 parts by weight, such as 0.1, 0.3, 0.5, 0.8, 1 parts by weight or any value therebetween; the content of the inorganic filler is preferably 30-60 parts by weight, such as 30, 35, 40, 45, 50, 55, 60 parts by weight or any value therebetween; the content of the auxiliary agent is preferably 0-20 parts by weight, such as 0, 2, 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween.

[0012] In the present invention, the ionic conductivity of the solid electrolyte at room temperature is preferably 10 -4S / cm or more, and its source and type can be various existing options. Specifically, the solid electrolyte is an oxide solid electrolyte and / or a sulfide solid electrolyte. Among them, the structural characteristics of the oxide solid electrolyte are preferably selected from at least one of NASICON type, garnet type and perovskite type, and specifically lithium oxide garnet (Li7La3Zr2O 12 , abbreviated as LLZO), (tantalum niobium) lithium lanthanum zirconate (Li 6.4 Ln3Z 1.4 (Ta,Nb) 0.6 O 12 , abbreviated as LLZXO), tin oxide (SnO2), bismuth oxide (Bi2O3), etc. The structural characteristics of the sulfide solid electrolyte are preferably at least one of amorphous, crystalline and glass ceramic types, and specific examples include lithium sulfide (Li2S), sodium sulfide (Na2S), sulfide (LPS, Li7P3S 11 ), lithium tetrathiophosphate sulfide (Li3PS4), etc. In addition, the particle size D50 of the solid electrolyte is preferably 0.3 to 30 μm, such as 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm or any value therebetween. When the particle size D50 of the solid electrolyte is within the above preferred range, it is more conducive to the uniform dispersion of the solid electrolyte in the epoxy resin adhesive system, giving it good electrical disassembly performance, and it is also more conducive to the reinforcing role of the solid electrolyte as a filler, and cooperating with other raw material components to improve the bonding strength, heat resistance and high temperature and high humidity resistance of the epoxy resin adhesive system. The term "D50" represents the particle size corresponding to the cumulative particle size distribution percentage of a sample reaching 50%.

[0013] In the present invention, the epoxy resin may be an aliphatic epoxy resin having two or more epoxy groups, or an aromatic epoxy resin having two or more epoxy groups, or a mixture of the two. The aliphatic epoxy resin having two or more epoxy groups may be at least one of an alicyclic epoxy resin, a glycidylamine epoxy resin, a hydantoin epoxy resin, an epoxy resin having a siloxane skeleton, and the like. Specific examples of the alicyclic epoxy resin include, but are not limited to, vinyl (3,4-cyclohexene) dioxide and / or 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-dioxane. The glycidylamine epoxy resin may be, for example, tetraglycidylbis(aminomethyl)cyclohexane. The hydantoin epoxy resin may be, for example, 1,3-diglycidyl-5-methyl-5-ethylhydantoin. The epoxy resin having a siloxane skeleton may be, for example, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane. The aromatic epoxy resin having more than two epoxy groups can be various existing epoxy resins with two epoxy groups and containing aromatic ring structures, and specific examples thereof include but are not limited to: at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, tetrabromobisphenol A epoxy resin, fluorene epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin, biphenyl epoxy resin, glycidylamine epoxy resin, naphthalene ring-containing epoxy resin, etc., and specifically at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, o-hydroxymethyl bisphenol A diglycidyl ether, dihydroxymethyl bisphenol A diglycidyl ether, tetrabromobisphenol A diglycidyl ether, resorcinol diglycidyl ether, pyrogallol triglycidyl ether pentaerythritol diglycidyl ether. If the epoxy resin is in a crystalline state, it is necessary to heat the epoxy resin to a non-crystalline state before use.

[0014] In the present invention, the type and source of the coupling agent can be various existing options, and can be selected from at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanate silane, and its specific examples include but are not limited to: γ-aminopropyl triethylsiloxane, γ-glycidoxypropyl trimethoxysiloxane, γ-methacrylate propyl trimethoxysiloxane, γ-mercaptopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, β-hydroxyethyl-γ-aminopropyl triethoxysiloxane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane. The addition of the coupling agent helps to promote the uniform dispersion of the solid electrolyte in the epoxy resin adhesive system, thereby facilitating the electrical disassembly performance of the epoxy resin adhesive system.

[0015] In the present invention, the type and source of the curing agent can be various existing options, for example, it can be selected from at least one of amine curing agents, acid anhydride curing agents and imidazole curing agents. The amine curing agent can be listed as at least one of aliphatic polyamines, alicyclic polyamines, piperazine-type polyamines and aromatic polyamines. Among them, the aliphatic polyamine can be listed as at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, triethanolamine, dicyandiamide, triethylenetetramine, tetraethylenepentamine, meta-xylylenediamine, trimethylhexamethylenediamine, and 2-methylpentamethylenediamine. The alicyclic polyamine can be listed as at least one of isophoronediamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, and 1,2-diaminocyclohexane. The piperazine-type polyamine can be listed as N-aminoethylpiperazine and / or 1,4-bis(2-amino-2-methylpropyl)piperazine. The aromatic polyamines include at least one of diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-diamino-3,3'diethyldiphenylmethane, bis(methylthio)toluenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenylsulfone, diethyltoluenediamine, trimethylenebis(4-aminobenzoate) and polytetramethylene oxide-diparaaminobenzoate. The anhydride curing agent includes at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, endomethyltetrahydrophthalic anhydride, alkenyl-substituted succinic anhydride, methylnadic anhydride and glutaric anhydride. Examples of the imidazole curing agent include 2-substituted imidazole compounds such as imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, and trimellitic acid imidazole salts such as 1-cyanoethyl-2-undecylimidazole. , at least one of triazine adducts such as 4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-dihydroxymethylimidazole.In addition, the optimal ratio of the curing agent is 0.6 to 1.3 equivalents relative to the epoxy equivalent of the epoxy resin.

[0016] In the present invention, the color powder can be any existing substance that can impart color to the epoxy resin adhesive without affecting its performance, and can be specifically selected from at least one of carbon black, iron oxide color powder, chromate color powder, cadmium color powder, ultramarine and phthalocyanine blue. Among them, the iron oxide color powder can be at least one of iron yellow, iron red and iron black. The chromate color powder can be chrome yellow and / or chrome green. The cadmium color powder can be cadmium red and / or cadmium yellow.

[0017] In the present invention, the inorganic filler can be any existing material that can improve the heat resistance, moisture resistance, electrical conductivity, thermal conductivity and other properties of the epoxy resin adhesive, and can specifically include at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talcum powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder. The average particle size of the inorganic filler is preferably 0.1 to 10 μm, such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value therebetween. In addition, the surface of the inorganic filler is preferably treated with a silane coupling agent, which can improve the compatibility of the inorganic filler with the epoxy resin adhesive system, and is more conducive to the improvement of the various properties of the epoxy resin adhesive. The specific treatment method can be any existing conventional selection, which can be known to those skilled in the art and will not be repeated here.

[0018] In the present invention, the type of the auxiliary agent is not particularly limited, and for example, the auxiliary agent may be selected from at least one of a defoaming agent, a leveling agent, a dispersant, and an antioxidant.

[0019] The preparation method of the epoxy resin adhesive provided by the present invention comprises uniformly mixing epoxy resin, solid electrolyte and coupling agent, and optional curing agent, color powder, inorganic filler and auxiliary agent to obtain epoxy resin adhesive. The present invention does not particularly limit the mixing conditions. In a preferred embodiment, the mixing method specifically comprises the following steps: uniformly mixing epoxy resin, solid electrolyte, coupling agent, and optional curing agent and color powder in a container by scraping the wall, adding inorganic filler to the obtained mixture and continuing to scrape the wall to mix uniformly, passing the obtained mixture through three rollers twice, and then transferring to a double planetary hybrid stirring kettle for stirring and mixing, and then vacuuming and degassing the obtained mixture, and sealing and storing it for standby after discharging.

[0020] The invention also provides application of the epoxy resin adhesive in bonding electronic products.

[0021] The present invention will be described in detail below through examples.

[0022] In the following examples and comparative examples, the raw materials and sources of the epoxy resin are as follows: bisphenol F diglycidyl ether, purchased from Mitsubishi Chemical Corporation, brand 806, epoxy equivalent of 160 g / eq; bisphenol A diglycidyl ether, purchased from Mitsubishi Chemical Corporation, brand 828, epoxy equivalent of 184 g / eq.

[0023] In the following examples and comparative examples, the raw materials and sources of the solid electrolyte are as follows: (tantalum niobium) lithium lanthanum zirconate, LLZXO, purchased from Shenzhen Kejing Zhida Technology Co., Ltd., product code 05021401, D50 is 300nm, and the ionic conductivity at room temperature is ≥7.0×10 -4 S / cm; Sulfide Li7P3S 11 , purchased from Shenzhen Kejing Zhida Technology Co., Ltd., with a particle size distribution of 0.5μm to 10μm, and an ionic conductivity of 2.0mS / cm at room temperature; lithium tetrathiophosphate sulfide Li3PS4, purchased from Shenzhen Kejing Zhida Technology Co., Ltd., with a particle size distribution of 0.5μm to 10μm, and an ionic conductivity of <10 at room temperature -8 S / cm; tin oxide (SnO2), purchased from Zhejiang Yamei Nanotechnology Co., Ltd., brand name AM-SnO2-028-1, D50 is 50nm; bismuth oxide (Bi2O3), purchased from Zhejiang Manli Nanotechnology Co., Ltd., brand name ML-Bi2O3-N50, D50 is 50nm; polyethylene oxide PEO solid electrolyte, purchased from Kruder Company, brand name E-30, ionic conductivity at room temperature is 6.29*10 -6 S / cm.

[0024] Example 1

[0025] S1. 25 parts by mass of bisphenol F diglycidyl ether, 15 parts by mass of LLZXO, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane and 0.5 parts by mass of carbon black were scraped and mixed in a container to obtain a premix;

[0026] S2. 50 parts by mass of silica was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0027] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0028] Example 2

[0029] S1. 32 parts by mass of bisphenol F diglycidyl ether, 5 parts by mass of LLZXO, 12 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane and 0.5 parts by mass of carbon black were scraped and mixed in a container to obtain a premix;

[0030] S2. 50 parts by mass of silica was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0031] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0032] Example 3

[0033] S1. 21 parts by mass of bisphenol F diglycidyl ether, 20 parts by mass of LLZXO, 8 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane and 0.5 parts by mass of carbon black were scraped and mixed in a container to obtain a premix;

[0034] S2. 50 parts by mass of silica was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0035] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0036] Example 4

[0037] S1. 25 parts by mass of bisphenol A diglycidyl ether, 15 parts by mass of LLZXO, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-mercaptopropyl trimethoxysiloxane and 0.5 parts by mass of carbon black were scraped and mixed in a container to obtain a premix;

[0038] S2. 50 parts by mass of calcium carbonate was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0039] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0040] Example 5

[0041] S1. 25 parts by mass of bisphenol F diglycidyl ether, 15 parts by mass of Li7P3S11 sulfide, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyltrimethoxysiloxane and 0.5 parts by mass of carbon black are scraped and mixed uniformly in a container to obtain a premix;

[0042] S2. 50 parts by mass of silica was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0043] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0044] Example 6

[0045] S1. 25 parts by mass of bisphenol F diglycidyl ether, 15 parts by mass of Li3PS4 sulfide, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-aminopropyl triethylsiloxane and 0.5 parts by mass of carbon black were scraped and mixed in a container to obtain a premix;

[0046] S2. 50 parts by mass of silica was added to the premix and scraped and mixed evenly over three rollers twice to obtain a mixture;

[0047] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy resin adhesive.

[0048] Example 7

[0049] An epoxy resin adhesive was prepared according to the method of Example 2, except that LLZXO was replaced by tin oxide (SnO2) in the same amount by mass, and the remaining conditions were the same as those of Example 2 to obtain an epoxy resin adhesive.

[0050] Example 8

[0051] An epoxy resin adhesive was prepared according to the method of Example 2, except that LLZXO was replaced by the same mass fraction of bismuth oxide (Bi2O3). The remaining conditions were the same as those of Example 2 to obtain an epoxy resin adhesive.

[0052] Comparative Example 1

[0053] An epoxy resin adhesive was prepared according to the method of Example 2, except that LLZXO was replaced by bisphenol F diglycidyl ether in the same mass fraction, and the remaining conditions were the same as in Example 2 to obtain an epoxy resin adhesive.

[0054] Comparative Example 2

[0055] An epoxy resin adhesive was prepared according to the method of Example 2, except that the amount of bisphenol F diglycidyl ether was 36 parts by mass and the amount of LLZXO was 1 part by mass, that is, the mass ratio of epoxy resin to solid electrolyte was 100:2.8, which was lower than the lower limit of the present invention, and the other conditions were the same as in Example 2 to obtain an epoxy resin adhesive.

[0056] Comparative Example 3

[0057] An epoxy resin adhesive was prepared according to the method of Example 2, except that LLZXO was replaced by an equal weight portion of polyethylene oxide (PEO) solid electrolyte. The remaining conditions were the same as those of Example 2 to obtain an epoxy resin adhesive.

[0058] Test Case

[0059] The epoxy resin adhesives obtained in the above examples and comparative examples were tested for bonding performance, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following methods. The results are shown in Table 1.

[0060] (1) Bonding strength test before power on: Use a glue dispenser to dispense the epoxy resin adhesive obtained in the examples and comparative examples at 110°C, apply a 25mm*4mm rectangular glue line on a stainless steel substrate, and then bond another stainless steel substrate to the stainless steel substrate. After bonding, cure the sample in an environment of 165°C for 2h to obtain a sample to be tested. Use a universal material testing machine to run the sample to be tested along the shear direction at a speed of 10mm / min until the sample fails to bond, record the maximum force value displayed by the instrument, and calculate the shear bonding strength of the adhesive to the stainless steel substrate in combination with the bonding area.

[0061] (2) Bonding strength after power-on: After the glue is dispensed and cured according to the method in (1), the sample to be tested is obtained. The positive and negative wires of the DC power supply are clamped at the two ends of the sample respectively. The power is applied at a voltage of 48 V or 60 V for 30 min or 20 min. After the power-on is completed, the sample is removed and the sample to be tested is run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated based on the bonding area (when the bonding strength is less than 2 MPa, it is removable).

[0062] (3) Heat resistance (80°C): After curing the adhesive according to the method in (1), the sample to be tested was obtained. The bonded sample was placed in an oven at 80°C for 20 min. Then, a universal material testing machine was used to run the prepared bonding sample in an environment of 80°C at a speed of 10 mm / min along the shear direction until the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.

[0063] (4) High temperature and high humidity resistance (85°C, 85% RH): The test sample was obtained after curing by the method in (1). The bonded shear sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample failed to bond. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.

[0064] Table 1

[0065]

[0066] It can be seen from the results in Table 1 that the epoxy resin adhesive provided by the present invention not only has high bonding strength, but also has good heat resistance and high temperature and high humidity resistance. At the same time, the bonding strength can be reduced to below 2 MPa after power is applied, that is, it has good detachability.

[0067] From the comparison between Example 2 and Comparative Example 1, it can be seen that when no solid electrolyte is added, although the obtained epoxy resin adhesive has a high bonding strength, the bonding strength remains at a high level after power is applied and cannot be reduced to below 2 MPa, that is, it does not have detachable properties.

[0068] From the comparison between Example 2 and Comparative Example 2, it can be seen that when the amount of solid electrolyte used is lower than the range of the present invention, not only the bonding strength, heat resistance and high temperature and high humidity resistance will be reduced, but also the bonding strength cannot be reduced to below 2MPa after power is applied, that is, it does not have detachable properties.

[0069] From the comparison between Example 2 and Comparative Example 3, it can be seen that when the solid electrolyte is selected as polyethylene oxide PEO solid electrolyte, not only the bonding strength, heat resistance and high temperature and high humidity resistance will be reduced, but also the bonding strength cannot be reduced to below 2MPa after power is applied, that is, it does not have detachable properties.

[0070] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An epoxy resin adhesive, characterized in that: The epoxy resin adhesive contains epoxy resin, solid electrolyte and coupling agent and optional curing agent, color powder, inorganic filler and additives; the solid electrolyte is an oxide solid electrolyte and / or a sulfide solid electrolyte; the mass ratio of the epoxy resin, solid electrolyte and coupling agent is 100:(10-150):(1-15).

2. The epoxy resin adhesive according to claim 1, characterized in that The content of the epoxy resin is 15 to 35 parts by weight, the content of the solid electrolyte is 5 to 20 parts by weight, the content of the coupling agent is 0.5 to 2 parts by weight, the content of the curing agent is 5 to 20 parts by weight, the content of the color powder is 0.1 to 1 part by weight, the content of the inorganic filler is 30 to 60 parts by weight, and the content of the auxiliary agent is 0 to 20 parts by weight.

3. The epoxy resin adhesive according to claim 1, characterized in that: The epoxy resin is an aromatic epoxy resin and / or an aliphatic epoxy resin.

4. The epoxy resin adhesive according to claim 1, characterized in that: The particle size D50 of the solid electrolyte is 0.3-30 μm.

5. The epoxy resin adhesive according to claim 1, characterized in that: The structural characteristics of the oxide-based solid electrolyte are selected from at least one of NASICON type, garnet type and perovskite type.

6. The epoxy resin adhesive according to claim 1, characterized in that: The structural characteristics of the sulfide solid electrolyte are selected from at least one of amorphous, crystalline and glass-ceramic types.

7. The epoxy resin adhesive according to claim 1, characterized in that: The coupling agent is selected from at least one of γ-aminopropyl triethylsiloxane, γ-glycidoxypropyl trimethoxysiloxane, γ-methacrylate propyl trimethoxysiloxane, γ-mercaptopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, β-hydroxyethyl-γ-aminopropyl triethoxysiloxane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane.

8. The epoxy resin adhesive according to claims 1 to 7, characterized in that: The curing agent is selected from at least one of an amine curing agent, an acid anhydride curing agent and an imidazole curing agent; Preferably, the toner is selected from at least one of carbon black, iron oxide toner, chromate toner, cadmium toner, ultramarine and phthalocyanine blue; Preferably, the inorganic filler is selected from at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talc powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder; Preferably, the auxiliary agent is selected from at least one of a defoamer, a leveling agent, a dispersant and an antioxidant.

9. The method for preparing the epoxy resin adhesive according to any one of claims 1 to 8, characterized in that: The method comprises the steps of uniformly mixing epoxy resin, solid electrolyte, coupling agent, optional curing agent, color powder, inorganic filler and auxiliary agent to obtain epoxy resin adhesive.

10. Use of the epoxy resin adhesive according to any one of claims 1 to 8 in bonding electronic products.